COMPARATIVE ASSESSMENT OF THE EFFECTIVENESS OF VARIOUS DRUGS FROM THE GROUP OF Α1-ADRENERGIC BLOCKERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
This article describes the effectiveness of various α-blocker drugs. According to in vitro studies, the affinity of silodosin for α1A receptors is more than 160 times greater than the affinity of this drug for α1B receptors and more than 50 times for α1D receptors. The selectivity of silodosin for α1A receptors is approximately 17 times higher than that of tamsulosin. According to the results of a double-blind randomized study, silodosin is not inferior in effectiveness to tamsulosin. According to the results of the studies, silodosin showed high effectiveness in the treatment of benign prostatic hyperplasia and a completely acceptable safety profile.